2017
DOI: 10.3748/wjg.v23.i41.7415
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of postoperative adjuvant transcatheter arterial chemoembolization in hepatocellular carcinoma patients with microvascular invasion

Abstract: AIMTo investigate the efficacy and safety of postoperative adjuvant transcatheter arterial chemoembolization (PA-TACE) in preventing tumor recurrence and improving survival in Barcelona Clinic Liver Cancer (BCLC) early (A) and intermediate (B) stage hepatocellular carcinoma (HCC) patients with microvascular invasion (MVI).METHODSA total of 519 BCLC A or B HCC patients treated by liver resection alone or followed by PA-TACE between January 2012 and December 2015 were studied retrospectively. Univariate and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 47 publications
4
60
1
Order By: Relevance
“…Adjuvant TACE could therefore decrease the recurrence risk with chemotherapy drugs and block the blood supply of “residual lesions” . In fact, a recent study also suggested a favorable effect of three cycles of adjuvant TACE on the prognosis in HCC patients with mVI . However, the authors did not elaborate on whether the treatment effect was consistent in patients with different characteristics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Adjuvant TACE could therefore decrease the recurrence risk with chemotherapy drugs and block the blood supply of “residual lesions” . In fact, a recent study also suggested a favorable effect of three cycles of adjuvant TACE on the prognosis in HCC patients with mVI . However, the authors did not elaborate on whether the treatment effect was consistent in patients with different characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…We performed adjuvant TACE only once at 4–6 weeks after surgery to minimize the adverse effects of this procedure in depressing the host immunity and damaging liver function . Some studies also achieved satisfactory results in patients with or without mVI by repeating this treatment twice or more. Recently, a meta‐analysis, including 3,325 patients, demonstrated that patients' prognosis was not improved by repeated courses .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed MVI to be a poor prognostic factor of tumor recurrence and long‐term survival after R0 LR . There is still no universally accepted adjuvant therapy after R0 LR for patients with HCC with MVI, although adjuvant therapies have been shown to be beneficial in selected patients . The best way to select these patients for postoperative adjuvant therapy remains to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, MVI can guide on whether to perform liver transplantation beyond Milan Criteria, anatomical liver resection, widening of the surgical margin, and neoadjuvant chemotherapy. [7][8][9][10] Therefore, it is of great significance to predict the risk of MVI in HCC before surgery.…”
Section: Introductionmentioning
confidence: 99%